Spatial and temporal distribution of bovine herpesvirus 1 transcripts. - Wirth, U V (1989)
Northern (RNA) blot analysis was used to determine the spatial and temporal distribution of bovine herpesvirus 1 (BHV-1) transcripts. Total RNA was isolated from Madin-Darby bovine kidney cells which had been infected with BHV-1.2b strain K22 or BHV-1.1 strain Jura in the presence or absence of metabolic inhibitors. Cloned restriction fragments representing the entire genome of strain K22 were labeled with 32P and hybridized to immobilized RNA. A total of 54 BHV-1 transcripts were found, ranging in size from 0.4 to larger than 8 kilobases (kb). The inverted repeat regions and an adjacent segment of the unique large part of the BHV-1 genome encoded three major immediate-early (IE) transcripts and one minor IE transcript enriched after cycloheximide treatment of infected cells. Late transcripts were identified by drastically reduced abundance after cytosine arabinoside (araC) treatment. Twelve late transcripts were encoded mainly by the unique long genome region, with a cluster of four transcripts located on HindIII fragment K (map units 0.677 to 0.733). The 21 transcripts unaffected by araC treatment were defined as early; they showed dispersed locations over the whole genome, with a cluster on the unique short sequence. The 17 remaining transcripts could not be classified unambiguously as early or late by these techniques. The IE transcript with a size of 4.2 kb exhibited homology with the single IE gene of pseudorabies virus, and the IE transcript with a size of 2.9 kb was encoded in part by the genome region known to be transcriptionally active during latency.